Combined Free Tissue Transfer for the Management of Composite Achilles Defects: Functional Outcomes and Patient Satisfaction following Thigh-Based Vascularized Reconstruction with a Neotendon Construct - DeFazio, Michael V.; Han, Kevin D.; Iorio, Matthew L.; Attinger, Christopher E.; Steinberg, John S.; Kim, Paul J.; Nemets, Laura; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2014)
Background Functional outcomes and quality-of-life measures following salvage reconstruction of composite Achilles/posterior leg defects are limited. We present our experience with combined Achilles defect reconstruction utilizing free tissue transfer with vascularized neotendon constructs.Methods Between 2011 and 2012, six patients underwent vascularized reconstruction of complex Achilles defects by a single surgeon. Demographic and functional data were collected for each patient. Subjective evaluation and quality-of-life measures were obtained preoperatively and postoperatively using American Orthopaedic Foot and Ankle Score (AOFAS) Ankle-Hindfoot and SF-36 scores. Early and late complications were noted for each case.Results All defects were reconstructed utilizing vascularized composite free tissue from the thigh. Average soft tissue defect was 76.7 cm2 (range, 40–90 cm2) with a tendon gap of 7.8 cm (range, 5–10 cm). Mean follow-up was 17 months (range, 15–23 months). Flap survival was 100%. Overall range of motion of the reconstructed side was 82% of the unaffected side (48.2 degrees vs. 59 degrees, p = 0.004). Average percent increase in AOFAS and SF-36 scores were 71% (54 vs. 93, p = 0.0005) and 22% (86 vs. 104, p = 0.003), respectively. Operative revision was required for two patients with delayed-onset soft tissue infections and one donor site hematoma. Distal flap ischemia was managed with hyperbaric oxygen therapy in one patient. Functional and esthetic outcomes were judged good to excellent by all patients.Conclusions Free tissue transfer with vascularized tendon reconstruction is a viable option for combined Achilles tendon/posterior leg defects, as both functional and quality-of-life measures appeared to be significantly improved at 1-year follow-up.
Keywords: Achilles tendon defects; composite tissue transfer; functional outcomes; patient satisfaction; quality-of-life measures